Telemedicine in heart failure—more than nice to have? - Eurlings, C. G. M. J. (Neth Heart J, 2018)
Telemedicine in chronic diseases like heart failure is rapidly evolving and has two important goals: improving and individualising care as well as reducing costs. In this paper, we provide a critical and an updated review of the current evidence by discussing the most important trials, meta-analyses and systematic reviews. So far, evidence for the CardioMEMS device is most convincing. Other trials regarding invasive and non-invasive telemonitoring and telephone support show divergent results, but several meta-analyses and systematic reviews uniformly reported a beneficial effect. Voice-over systems and ECG monitoring had neutral results. Lack of direct comparison between different modalities makes it impossible to determine the most effective method. Dutch studies showed predominantly non-significant results, mainly due to underpowered studies or because of a high standard of usual care. There are no conclusive results on cost-effectiveness of telemedicine because of the above shortcomings. The adherence of elderly patients was good in the trials, being essential for the compliance of telemedicine in the entire heart failure population. In the future perspective, telemedicine should be better standardised and evolve to be more than an addition to standard care to improve care and reduce costs.